2005
DOI: 10.1093/aje/kwi158
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Background Levels of Polychlorinated Biphenyls and Cognitive Functioning among School-age Children

Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous environmental contaminants. In utero exposure to background levels of PCBs has been associated with intellectual impairment among children in most, but not all, studies. The authors evaluated prenatal PCB exposure in relation to cognitive test (intelligence quotient (IQ)) scores on the Wechsler Intelligence Scale for Children at age 7 years. Pregnant women were recruited from 12 US study centers from 1959 to 1965, and their children were followed until age 7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 38 publications
5
54
2
Order By: Relevance
“…Lead exposure was a public health concern in Baltimore during the 1960s and 1970s and even blood lead concentrations of <10 µg/ dl have been implicated in poorer cognitive performance (16). Nevertheless, the mean IQ in this study is consistent with averages observed in a study of nationwide CPP data (17,18).…”
Section: Articlessupporting
confidence: 87%
“…Lead exposure was a public health concern in Baltimore during the 1960s and 1970s and even blood lead concentrations of <10 µg/ dl have been implicated in poorer cognitive performance (16). Nevertheless, the mean IQ in this study is consistent with averages observed in a study of nationwide CPP data (17,18).…”
Section: Articlessupporting
confidence: 87%
“…environmental exposure has been reported to be associated with altered psychomotor development in children and lower birth weight and size in newborns ( Hertz-Picciotto et al, 2005;Koopman-Essenboom et al, 1996;Sagiv et al, 2007;Sala et al, 2001), although other studies have either not confirmed these findings or found that such effects do not persist into toddler and school aged children (Gladen and Rogan, 1991;Gray et al, 2005;Hertz-Picciotto et al, 2005;Koopman-Essenboom et al, 1996;Wolff et al, 2007). Many animal studies demonstrate that high dose PCB impairs neurodevelopment or their hydroxylated metabolites may interfere with thyroid hormone-dependent neurodevelopment (Kimura-Kuroda et al, 2007;Nguon et al, 2005;Purkey et al, 2004;Roegge et al, 2006).…”
Section: Geometric Selected Percentilesmentioning
confidence: 99%
“…Relationship 3: prenatal PCB body burdens and neurocognitive outcomes We found 8 studies that directly assessed maternal PCB body burdens and cognitive outcomes in children (Gray et al, 2005;Jacobson, 1996, 2003;Jacobson et al, 1990;Patandin et al, 1999;Stewart et al, 2008;Vreugdenhil et al, 2002;Stewart et al, 2003) (see Table 3). Five met our inclusion criteria (Gray et al, 2005;Jacobson et al, 1990;Patandin et al, 1999;Stewart et al, 2008;Vreugdenhil et al, 2002).…”
Section: Maternal Thyroidmentioning
confidence: 99%
“…We obtained a slope for the relationship between FT 4 and IQ in Haddow et al (1999) by simulating the population distribution of FT4 and IQ in case and control groups (see Supplementary Material for more Jacobson et al (1990), and Vreugdenhil et al (2002) used models with a log-transformed sum of PCB concentration as the independent variable. Gray et al (2005) and Stewart et al (2008) used linear models. We converted their slopes using log-transformed PCBs as the independent variable.…”
Section: Model For Relationship 2: Prenatal Ft 4 Levels and Neurocognmentioning
confidence: 99%